Effect of tin mining waste as sand replacement on flowability and compressive strength of mortar - Noraziah, Ahmad; Khairunisa, Muthusamy; H. N., Ruslan; Mohd Yusri, Mohd Yunus; M. A., Ismail (IOP Publishing, 2024)
Environmental degradation due to excessive sand mining activity and tin tailing waste disposal from mining need to be resolved. Utilization of tin tailing as sand replacement in mortar production would cut amount of waste thrown and decrease river sand consumption. The current study examines the effect of tin tailing content sand replacement on flowability and strength of mortar. Five forms of mixes were produced using different percentage of tin tailing as fine aggregate replacement. Two types of tests were conducted namely flowability test and compressive strength test. The investigation discovers that blending tin tailing affects the flowability of mortar. Utilization of up to 30% tin tailing able to produce mortar with the targeted strength. Usage of high amount of tin tailing causes declination of mortar strength. Recycling tin tailing for use in mortar production saves the use of natural sand and reduce waste disposal.